2009
DOI: 10.5539/jsd.v2n1p121
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Epiphytes Diversity at Pusat Sejadi, Kawang Forest Reserve, Sabah Malaysia

Abstract: Vascular epiphyte category as well as diversity of epiphytic was studied in Pusat Sejadi, Kawang Forest Reserve Papar Sabah. Five randomly sampling plots of 50m x 40m (0.2 ha) were presented for 1 ha of the forest for the purposed of data collection. The result showed that 3 types of phorophytes (host tree) on which the vascular epiphyte attached to: standing tree, dead standing tree and fallen tree (deadwood). The standing and dead standing tree were subdivided into 3 zones which known as basal part, trunk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Accordingly, those epiphytes occurring in dense stands were counted as a single individual. The vertical distribution of vascular epiphytes on the phorophytes was studied following Mojiol et al [18] zonation. Accordingly, host trees were partitioned into three zones: (1) basal region, from the ground to the diameter at breast height (at or below 3 m above ground level); (2) trunk region, from diameter at breast height (to the first branch/above 3 m and below the first branch); and (3) canopy region, from first branch to tip of the tree.…”
Section: Data Collectionmentioning
confidence: 99%
“…Accordingly, those epiphytes occurring in dense stands were counted as a single individual. The vertical distribution of vascular epiphytes on the phorophytes was studied following Mojiol et al [18] zonation. Accordingly, host trees were partitioned into three zones: (1) basal region, from the ground to the diameter at breast height (at or below 3 m above ground level); (2) trunk region, from diameter at breast height (to the first branch/above 3 m and below the first branch); and (3) canopy region, from first branch to tip of the tree.…”
Section: Data Collectionmentioning
confidence: 99%
“…To validate further Chi-square correlation test was performed which showed a significant correlation with epiphytic orchids Frequency Growth Zone preferring trunk and canopy (X 2 (1) = 14.76, p< .05). As per Mojiol et al (2009), the zonation method of epiphytic orchids reveals that species is abundant in the canopy zone than at the base and trunk of the host tree. Furthermore, (Sillet,1999;Doverspike, 2017), reported that the presence of branches in the canopy layer may result in an accumulation of dust, which encourages epiphytes to grow.…”
Section: Figure 8 Canopy Coverage and The Frequency Of Orchidsmentioning
confidence: 94%
“…host tree and growth zones) on host trees were also recorded. The epiphyte's growth position on the host tree was determined by using the zonation method where the host trees were partitioned into three zones: Zone (1) = Basal, from the ground to the diameter at breast height (dbh), Zone (2) = Trunk (from the dbh to the first branch and Zone) (3) = Canopy, (from the first branch to the tip of the tree) (Mojiol et al, 2009). The site factors like latitude, longitude, altitude, aspect, slope, bark texture, and canopy cover were also recorded.…”
Section: Sampling Designmentioning
confidence: 99%
See 1 more Smart Citation